Muscle Development in the Late Embryonic and Early Post-Hatch Poult - Moore, D.T.; Ferket, P.R.; Mozdziak, P.E. (International Journal of Poultry Science, 2005)
Satellite cells are mitotically active cells in skeletal muscle that contribute new nuclei to growing myofibers. The objective of this experiment was to determine satellite cell mitotic activity in turkey embryos, early post-hatch poults, and 1 week-old poults. All poults were fed a standard corn and soybean meal based starter diet throughout the experiment. 5-bromo-2`deoxyuridine (BrdU) was injected intra-abdominally into all poults and embryos. Pectoralis thoracicus were harvested two hours post-injection to determine mitotically active satellite cells. Samples were taken at 25 days of incubation (25E), day-of-hatch, 1 day-of-age, and 1 wk-of -age (n = 10 for all groups). BrdU immunohistochemistry along with computer-based image analysis was used to identify the mitotically active satellite cells. Satellite cell mitotic activity was lower (P < 0.05) at 25E compared to day of hatch. Furthermore, there was an age-related decrease (P < 0.05) in satellite cell mitotic activity between 1 day posthatch to one week-of-age. The low satellite cell mitotic activity at 25E suggests that late embryonic development may be a developmental period to target increasing satellite cell mitotic activity. Furthermore, the normally high satellite cell mitotic activity immediately post-hatch suggests that the early post-hatch period is also an important target for nutritional manipulations aimed at improving skeletal muscle growth and meat yield.